(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
Through technical progress and the further development of smaller and more navigable treatment instruments, it is now possible to treat small peripheral vascular diseases with a diameter of less than 2 mm, such as chronic subdural hematom caused by the middle meningeal artery, with neurointerventional procedures. These procedures are technically very difficult and require systematic learning by the physicians. This paper describes the development and manufacturing of a first middle meningeal artery model for the treatment simulation of chronic subdural hematoma, which is to be integrated into the existing neurointerventional simulator HANNES. The first 3D printed model enables learning and training in catheterization the small vessels.